2006
DOI: 10.1007/s10549-006-9215-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the insulin-like growth factor-1 system and the oestrogen metabolising enzymes in breast cancer tissue and its adjacent non-cancerous tissue

Abstract: IGF-1R is over-expressed in malignant tissue. IGF-1 is expressed at higher levels in ER positive tumours probably as a result of oestrogen stimulation while IGF-1R expression is higher in ER negative samples as an adaptation to lower local IGF-1 levels. An IGF-1 paracrine relationship may exist between tumour and ANCT but for STS and Cyp-19, there may be an autocrine-paracrine relationship. The IGF-1 ligand-receptor system is an important regulator of oestrogen production while oestrogen may be involved in sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 85 publications
5
11
1
Order By: Relevance
“…this result is consistent with previously described data obtained in mice, where the overexpression of IGF1R facilitated tumor development (36,37). Moreover, increased expression of IGF1R has been linked to several cancer types in humans (38,39). It has been proposed that the up-regulation of iGF1r in cancer cells may be due to loss of transcriptional control by major tumor-suppressor genes (40).…”
Section: Discussionsupporting
confidence: 92%
“…this result is consistent with previously described data obtained in mice, where the overexpression of IGF1R facilitated tumor development (36,37). Moreover, increased expression of IGF1R has been linked to several cancer types in humans (38,39). It has been proposed that the up-regulation of iGF1r in cancer cells may be due to loss of transcriptional control by major tumor-suppressor genes (40).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with TFF1 and PGR being known to be regulated by estrogen and the presence of higher levels of ESR1 in the malignant tissue than in adjacent normal tissue. We did not see any significant differences in the expression of CYP19, HSD17B1, and HSD17B2 between normal breast and malignant tissues, in agreement with the results of other studies of more heterogeneous patient groups (42,44,45). The consistent finding that CYP19 does not show increased expression in tumor compared with normal tissue may be a reflection of its very low activity within the breast, which makes accurate measurement of CYP19 mRNA, protein, or enzyme activity difficult.…”
Section: Discussionsupporting
confidence: 90%
“…IGF1R expression was detected in a higher proportion of luminal A tumors, followed by luminal B and HER2-positive tumors, with the lowest rate in basal/triple-negative, in line with previous investigators who reported co-expression of IGF1R and ER signaling systems. 19,24,25,32 The presence of IGF1R in tumors with higher content of ER/PR support the development of a subset of breast carcinoma subtypes along these two distinct pathways, mainly luminal A and B. It is plausible that together with microenvironment interactions and/or additional gene alterations, it might contribute to tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Recent epidemiological and clinico-pathological data have supported the role of the insulin-like growth factor-1 (IGF1R) signaling system on tumor development and progression. [13][14][15][16][17] In breast carcinoma, high levels of IGF1R have been detected in 30-82%, 18,19 but its prognostic value is controversial. [20][21][22][23][24][25][26][27] Emerging experimental and clinical data suggest that the IGF1R and ER/PR pathways are interactive.…”
mentioning
confidence: 99%